Plankton Diversity In The Labuhanbatu Bilar River - Ika Rosenta Purba; Arman Harahap (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
The purpose of this study was to determine the plankton diversity index in the Labuhanbatu Bilah River. The research was carried out from January to March 2023 using the Purposive Random Sampling method which consisted of 3 observation stations, namely station 1. There were many community activities such as Domestic Waste, Sand Mining, Agriculture, Station 2. There was Domestic Waste, Cage Fish Farming and Agriculture. and Station 3. There are community activities such as bathing, domestic and agricultural waste. The results of the study found that the plankton composition in the Bilah Labuhanbatu River consisted of 3 classes of phytoplankton, namely Bacillariophyceae, Chlorophyceae and Cyanophyceae while the class of zooplankton consisted of 4 classes, namely Mastigophora, Monogononta, Crustacea and Ciliophora. The highest diversity index of phytoplankton was obtained at station 1 of the sand mining area with a value of 1.76 indicating that the level of diversity was included in the medium category. In zooplankton the highest diversity index was found at station 3 with a value of 0.42 which indicated that the level of diversity was included in the low category. Meanwhile, the highest dominance index for phytolactones was found at station 3 in a densely populated area with a value of 0.51, while for zooplankton it was found at station 1 in a sand mining area with a value of 0.00487, both values ​​indicating that no plankton genus dominates in the area. In zooplankton the highest diversity index was found at station 3 with a value of 0.42 which indicated that the level of diversity was included in the low category. Meanwhile, the highest dominance index for phytolactones was found at station 3 in a densely populated area with a value of 0.51, while for zooplankton it was found at station 1 in a sand mining area with a value of 0.00487, both values ​​indicating that no plankton genus dominates in the area. In zooplankton the highest diversity index was found at station 3 with a value of 0.42 which indicated that the level of diversity was included in the low category. Meanwhile, the highest dominance index for phytolactones was found at station 3 in a densely populated area with a value of 0.51, while for zooplankton it was found at station 1 in a sand mining area with a value of 0.00487, both values ​​indicating that no plankton genus dominates in the area.